Employer Cooperation, Productivity, and Wages: New Evidence from Inter-Firm Formal Network Agreements - Francesco Devicienti; Elena Grinza; Alessandro Manello; Davide Vannoni (Institute of Labor Economics (IZA), 2022)
Using uniquely rich administrative matched employer-employee data, we investigate the impact of formal network agreements (FNAs) among firms under two perspectives. First, we assess the impact of joining a FNA on several indicators of firm performance, and total factor productivity. Second, we investigate whether and how such effects are transmitted to the workers, in terms of wage changes. On the firm-level side, we find an overall significant and economically relevant positive effect of FNAs on firm performance, which resists a large set of robustness tests. However, such a positive effect on firms does not translate into tangible benefits for the workers, on average. After estimating an array of multiple-way fixed effects wage regressions, we find a negative, though small, wage effect. Moreover, we detect a rather marked heterogeneity in the impacts on both firms and workers. The estimation of rent-sharing equations, as well as other tests that exploit unionization data, suggest that the negative effects on wages might be explained by a decrease in workers' bargaining power following the introduction of FNAs.
Keywords: L14; D24; J31; 330; Inter-firm cooperation; formal network agreements; firm performance; total factor productivity (TFP); wages; matched employer-employee data